Implementation of Regulations to Strengthen the Role of Village Consultative Bodies in Drafting Village Regulations for Economic Potential Development in Tarumajaya District, Bekasi Regency - Siti Nur Intihani; Slamet Riyanto; Damrah Mamang (Universitas Djuanda, 2026)
The Village Consultative Body (BPD) is a governmental institution whose members represent village residents based on territorial representation and are democratically appointed. The BPD plays a pivotal role in developing village economic potential, with one of its main functions being the drafting of village regulations (Perdes). This study seeks to examine the implementation of regulatory functions of the BPD in drafting Perdes and to assess the capacity-building efforts for BPD members in formulating Perdes for economic development in Tarumajaya District, Bekasi Regency. The research employed a combined normative juridical and empirical approach, with a review of relevant literature, followed by field observations in seven villages in Tarumajaya, interviews with stakeholders, and Focus Group Discussions (FGDs). The findings revealed that: (1) the implementation of BPD’s regulatory functions in formulating Perdes on economic development across the seven villages in Tarumajaya remained suboptimal. The challenges identified included: (a) limited expertise of BPD members in legal drafting, (b) insufficient capacity to analyze village economic potential, and (c) an unconducive working climate between village heads and the BPD. (2) Optimizing the capacity of BPD members in drafting Perdes on economic development was achieved through: (a) updating regulations concerning recruitment patterns and membership requirements of the BPD, (b) organizing training and workshops to strengthen members’ legal drafting skills, (c) providing mentoring and technical assistance through model templates of village regulation draft (Raperdes) to serve as references, and (d) fostering collaboration with academics and non-governmental organizations.